FINANCIAL PERFORMANCE ANALYSIS OF CONSTRUCTION STATE-OWNED ENTERPRISES LISTED IN INDONESIA STOCK EXCHANGE DURING COVID-19 - Nugroho Setyo Utomo; Sylvia Sandyazmara Devi; Hermanto Siregar (Univeristas Islam Bandung, 2022)
Construction State-Owned Enterprises (SOEs) have a very critical role in achieving the Government’s goal in infrastructure development, in order to increase the efficiency of production line, transportation and support economic growth and equitable development in Indonesia. The priority of development has driven around 3,26 times in total asset growth of four construction SOEs listed in Indonesia Stock Exchange (IDX), from IDR 85,88 trillion (2015) to IDR 280,38 trillion (2019), but facing challenges since pandemic Covid-19 in 2020. This study aims to analyze the financial performance of these construction SOEs during Covid-19. The descriptive analysis of financial performances of construction SOEs for year 2016 to 2021, pre and during pandemic Covid-19 was used in this study with three approaches: Ministerial Decree of SOEs No. KEP-100/MBU/2002 about financial soundness assessment of SOEs, Altman Z-Score (1968 and 2006 model) and Debt Service Cover Ratio (DSCR). The managerial implication of this study is to predict the financial resilience of these construction SOEs in facing challenges in upcoming years.